Institution, normalisering, vetande (Sociologisk Forskning, 1993)
Institution, normalization, knowledgeNormalization, as strategy and process of social correction of the non-normal, is threefold. Firstly, there is normalization by pleas; attempts to normalize powerful social forces that behave non-normally by referrals to norms and rules of the game. The second kind of normalization hinges on the material power of institutions. In the human services, these power practices are related to discursive systems in psychiatry, penology, child psychology and the like. The third kind is the one most similar to normal socialization, that is exposing the non-normal to normal contexts. Increasingly, pre-modern institutions ofthe second kind are discontinued, and new discourse dependent social enclosures of the contextual normalizing kind are initiated.